1998
DOI: 10.3346/jkms.1998.13.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of IgE response to TDI-HSA conjugates by ELISA in toluene diisocyanate (TDI)-induced occupational asthma (OA) patients

Abstract: Toluene diisocyanate (TDI), a low molecular weight reactive chemical, is known to be a main cause of occupational asthma (OA) in Korea. Although it is thought that inhaled TDI may act as a hapten, the precise mechanisms of TDI-induced OA are unknown. In this study, TDI-human serum albumin (HSA) conjugates (5, 10, 20 and 30 min) were prepared in the range of 1.5 to 5.0 TDI mole/HSA mole. Specific binding of serum IgE to TDI-HSA (30 min) was observed using IgE ELISA as well as ELISA inhibition assay. Around 40% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…[10][11][12] Antigenicity of isocyanate-albumin conjugates prepared on the basis of the Scheel liquid phase exposure methodology has been reported to vary according to the degree of isocyanate-protein conjugation, with lightly or moderately substituted conjugates better recognized by IgE in limited human studies. [12][13][14] A similar phenomenon has been well-documented in animal models with other low-molecular-weight haptens, in which the degree of substitution affects immune recognition. 15,16 The generation of low substitution ratio isocyanate-albumin conjugates by methods published to date has been challenging because of numerous technical issues, including isocyanate's insolubility in aqueous solutions, reactivity with water, and fast reaction rate with proteins.…”
mentioning
confidence: 70%
“…[10][11][12] Antigenicity of isocyanate-albumin conjugates prepared on the basis of the Scheel liquid phase exposure methodology has been reported to vary according to the degree of isocyanate-protein conjugation, with lightly or moderately substituted conjugates better recognized by IgE in limited human studies. [12][13][14] A similar phenomenon has been well-documented in animal models with other low-molecular-weight haptens, in which the degree of substitution affects immune recognition. 15,16 The generation of low substitution ratio isocyanate-albumin conjugates by methods published to date has been challenging because of numerous technical issues, including isocyanate's insolubility in aqueous solutions, reactivity with water, and fast reaction rate with proteins.…”
mentioning
confidence: 70%
“…In contrast to classical IgE-mediated allergic responses, most diisocyanates studies show poor correlation between bronchial responses and the presence of specific IgE antibodies to diisocyanates. Only 40% of patients were positive for serum-specific IgE following human serum albumin conjugation [4]. Moreover, various types of inflammatory cells, including eosinophils, are involved in inflammation after diisocyanates binding to airway epithelial cells (AECs) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The preferential antigenic site on the conjugate was also considered. Several authors have suggested that hydrophilic groups reacting with the isocyanate might lead to changes in the three-dimensional conformation of the HSA and formation of new antigenic determinants (Wass and Belin, 1989;Son et al, 1998).…”
Section: Degree Of Modificationmentioning
confidence: 99%